Use of carotenoids in feed mixtures for poultry: a review - Marounek Milan; Pebriansyah Akhir (Agricultura Tropica et Subtropica, 2018)
Carotenoids are present in ingredients of feed for poultry. Their content can be further increased by supplementation of feed mixtures with synthetic or natural carotenoids. The present paper recapitulates knowledge on the use of carotenoids in broiler chickens and laying hens, and deals with synthetic or natural carotenoids derived from plants. The review describes effects of carotenoids on productive performance, oxidative stability of poultry products, colouring of yolks and accumulation of carotenoids in yolks. There are several alternatives to synthetic carotenoids which are usable in poultry diets and satisfy the interest of consumers in poultry products free of undesirable side effects.